Overcoming Challenges for Shoot Tip Cryopreservation of Root and Tuber Crops - Zhang, A.; Wang, M.; Li, Z.; Panis, B.; Bettoni, J.C.; Vollmer, R.; Xu, L.; Wang, Q. (MDPI, 2023)
Root and tuber crops (RTCs) are the second-most important carbohydrate commodity after cereals. Many species of the RTCs are vegetatively propagated, making their shoot tips the preferred material to be conserved for future uses. Shoot tip cryopreservation provides an important tool to support the long-term conservation of plant genetic resources. Over the past four decades, significant efforts have been undertaken to move shoot tip cryopreservation of RTCs from research projects to full-scale implementation in cryobanks. This comprehensive review focuses on the history of cryopreservation protocols developed in RTCs. The encapsulation and vitrification solution-based cryopreservation techniques followed by ultra-rapid freezing and thawing have been highly successful. Additionally, different strategies for improving the cryotolerance of shoot tips have been introduced to further increase post-cryopreservation recovery. Finally, the research conducted to explain the mechanism underlying cryoprotection and differential cryotolerance including the use of histological studies are highlighted.